Analysis of Sales Staff Work Ability and Service Quality on Guest Satisfaction at Openaire Resto Bar and Market - Cholisatul Husnah; Henry Yuliamir (Mahesa Research Center, 2025)
This study analyzes the influence of Sales Staff Work Ability and Sales Staff Service Quality on Guest Satisfaction in a hotel. The interaction between sales staff and guests plays a crucial role in shaping the customer experience. Therefore, this study identifies the most influential factors in increasing guest satisfaction. The approach used is quantitative descriptive and causal with purposive sampling, involving guests who interacted with sales staff in the past month. Data were collected through standardized questionnaires and analyzed using multiple linear regression. The results showed that both independent variables had a significant effect on guest satisfaction, with Sales Staff Service Quality providing a greater contribution. The regression equation obtained: Y = 6.181 + 0.090X1 + 0.705X2. The main factors that increase guest satisfaction are responsiveness, friendliness, professionalism, and attention to customer needs rather than simply product mastery. Limitations of the study include the limited scope of one hotel and the failure to consider other external factors that may affect guest satisfaction, such as price or hotel atmosphere. Further research is recommended to explore additional factors and expand the scope of locations in order to obtain more generalizable results.